(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
Anthropology is a science that has much to contribute to the study of criminal behavior, and in an effort to make visible the necessary relationship between the two, the development of a discipline within the field of Sociocultural Anthropology is proposed. Taking as an example the model of some countries such as Argentina, the involvement of Anthropology in the study of the criminal phenomenon is claimed, something that so far does not happen in Spain. There are many fields of study in which Anthropology could contribute enriching knowledge, in particular the study in the field of penitentiary centers and the resocializing purpose of custodial sentences. The objective is to carry out a bibliographic review of the research carried out in Spain on recidivism and its causes and to explore the relationship between the participation of prisoners in Restorative Justice and family mediation meetings and the impact it may have on the recidivism rate. The main contribution points out that the strengthening of social and family ties has a beneficial impact on criminal desistance and the reduction of recidivism. The Anthropology of crime provides a theoretical and methodological basis from which to make valuable contributions to the phenomenon of criminal recidivism and to propose new strategies aimed at improving the process of reentry into society of released prisoners.